Interaction effects of pen environment and sex on behavior, skin lesions and physiology of Windsnyer pigs - Mbusiseni Vusumuzi Mkwanazi; Arnold Tapera Kanengoni; Michael Chimonyo (Asian-Australasian Journal of Animal Sciences, 2019)
Objective The study was carried to determine the interaction effects of pen enrichment and sex on behavioral activities, skin lesions and physiology of Windsnyer pigs. Methods Forty-eight growing Windsnyer pigs of both sex, with an average initial body weight of 21.6 (±9.01) kg were used. Four pigs were randomly assigned to either enriched or barren pens at a stocking density of 0.35 m2/pig. Enriched pens contained 2 L bottles filled with stones and suspended at head level on ropes stretching across the pens. In addition, two plastic balls (90 mm in diameter) and 500 mL bottles (235 mm long) were placed on the floor of each enriched pen. Results Pigs in barren environments had higher heart rates (p<0.001) than those in enriched pens. There was an interaction of pen environment and sex on rectal temperature (p<0.001). Females in enriched pens had higher rectal temperatures (p<0.05) than females in barren pens. There was no interaction of pen environment and sex on time spent eating and drinking (p>0.05). Time spent bullying was influenced (p<0.05) by pen environment and sex. Female pigs in barren environment spent more time on bullying than females in enriched pens. There was an interaction of pen environment and sex on time spent lying down and walking (p<0.05). Female pigs in enriched pens spent more time lying down than females in barren pens. Males in barren pens spent more time walking than males in enriched pens while no effect of pen environment was observed in females. There was an interaction of pen environment and sex on the number of skin lesions in the head, neck and shoulder region and other parts of the body (p<0.05). Conclusion It was concluded that pen enrichment reduced the number of skin lesions and anti-social behaviors, especially for female pigs. There is a need, therefore of housing indigenous pigs under confinement.